Web-based field service system / Moon Ting Su, Hui Koon Chuah and Chai Ee Khoo - Moon, Ting Su; Hui, Koon Chuah; Chai, Ee Khoo (2004)
Companies are continuing to place more emphasis on all types of customer services, including field service. Field service is defined as the processes involved in servicing products in the field after they have been sold. It is a specialized subset of functions under the broad umbrella of Customer Relationship Management (CRM) and represents a growing market for software and solution vendors. This paper first presents the general processes that build up a service operation. This is followed by evaluation of current Field Service applications in the marketplace. Based on the analysis, Field Service System (FSS) is proposed. This system consists of five modules namely service call management, user management, sales management, dispatch management- and work order management. FSS provides the following functionalities scheduling of work among the field service workers, management of customers and parts information, reports generation and monitoring as well as measurement of field service activities. In addition, FSS is web-based thus providing access to field service functions from anywhere, anytime. It is developed using ASP.NET. The methodology employed, design and implementation of FSS are discussed. As a conclusion, FSS allows small and medium sized field service organizations to effectively manage their customer service